2015
DOI: 10.1371/journal.pone.0144831
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Bacteria Isolated from Bovine Mammary Microbiota: Potential Allies against Bovine Mastitis

Abstract: Bovine mastitis is a costly disease in dairy cattle worldwide. As of yet, the control of bovine mastitis is mostly based on prevention by thorough hygienic procedures during milking. Additional strategies include vaccination and utilization of antibiotics. Despite these measures, mastitis is not fully under control, thus prompting the need for alternative strategies. The goal of this study was to isolate autochthonous lactic acid bacteria (LAB) from bovine mammary microbiota that exhibit beneficial properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 39 publications
(56 reference statements)
2
79
0
3
Order By: Relevance
“…Several studies have shown a dramatic decrease in the bovine udder microbiome during mastitis, even after recovery [115][116][117]. It might be worthwhile to consider alternative prevention strategies like strengthening the natural udder microbiota that competes with pathogens [118].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a dramatic decrease in the bovine udder microbiome during mastitis, even after recovery [115][116][117]. It might be worthwhile to consider alternative prevention strategies like strengthening the natural udder microbiota that competes with pathogens [118].…”
Section: Discussionmentioning
confidence: 99%
“…Although some approaches show great promise for future treatment methods or at least for complemental therapy, there is no contemporary alternative available for in vivo administration (Gomes & Henriques, ). Several studies investigated the application of lactic acid bacteria (LAB) as mammary probiotics to inhibit in vitro growth of MCP, prevent or compete MCP biofilm formation or reduce IMI (Armas, Camperio, & Marianelli, ; Assis et al., ; Bouchard, Rault, Berkova, Le Loir, & Even, ; Bouchard et al., ; Piccart, Vásquez, Piepers, De Vliegher, & Olofsson, ).…”
Section: Alternative Therapeutic Approachesmentioning
confidence: 99%
“…Enumeration of LAB from either Bac + LAB- L. monocytogenes hotdog challenge studies, or as LAB contaminants in Bac + CFS- Listeria challenge studies, was done using MRS agar adjusted with HCl to pH 5.4–5.5 prior to autoclaving (the pH was found to be ~pH 5.5–5.7 after autoclaving) [24]. Acidified MRS agar inhibited growth of L. monocytogenes 39-2 but allowed the growth of LAB as determined from prior studies.…”
Section: Methodsmentioning
confidence: 99%